Subthalamic nucleus deep brain stimulation evokes resonant neural activity. Issue 5 (4th May 2018) - Sinclair, Nicholas C.; McDermott, Hugh J.; Bulluss, Kristian J.; Fallon, James B.; Perera, Thushara; Xu, San San; Brown, Peter; Thevathasan, Wesley
Abstract : Deep brain stimulation (DBS) is a rapidly expanding treatment for neurological and psychiatric conditions; however, a target‐specific biomarker is required to optimize therapy. Here, we show that DBS evokes a large‐amplitude resonant neural response focally in the subthalamic nucleus. This response is greatest in the dorsal region (the clinically optimal stimulation target for Parkinson disease), coincides with improved clinical performance, is chronically recordable, and is present under general anesthesia. These features make it a readily utilizable electrophysiological signal that could potentially be used for guiding electrode implantation surgery and tailoring DBS therapy to improve patient outcomes. Ann Neurol 2018;83:1027–1031